Sensory Acceptability of Puréed Foods - Jamila R. Lepore; Wendy J. Dahl (EDIS)
It is important that we enjoy the food we eat. This makes for a better quality of life. This is no different for those people needing to be on puréed diets due to swallowing problems. And just like you wouldn’t want to serve guests a recipe without trying it first, you don’t want to serve a puréed food without knowing that it is appealing. This 5-page fact sheet was written by Jamila R. Lepore and Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, November 2012.